Social and configural effects on the cognitive dynamics of perspective-taking. - Galati, Alexia; Dale, Rick; Duran, Nicholas D. (Journal of Memory & Language, 2019)
Highlights • We examine the impact of configural cues on perspective selection and its dynamics. • Other-centrism increased with other-aligned configural cues (consistent or inconsistent). • Response dynamics captured through mouse-tracking were predicted by strategy. • An egocentric (vs. other-centric) strategy involved shorter, more direct trajectories. • Still, configural cues contributed to the stabilization of the other-centric strategy. Abstract How do environmental cues and social perspectives influence perspective selection? Listeners responded to instructions (e.g., "Give me the folder on the right") from a simulated partner, selecting from two objects consistently aligned with themselves (ego-aligned; Experiment 1a) or the speaker (other-aligned; Experiment1b). In Experiment 2, listeners selected from triangular 3-object configurations whose orientation varied (ego-, other-, or neither-aligned). When the configural cue was other-aligned (consistently or inconsistently: Experiments 1b and 2), listeners were more likely to be other-centric. Other-centric responders stabilized their strategy more quickly when the cue was other-aligned, but their mouse trajectories did not exhibit facilitation (Experiment 1b vs. 1a). In Experiment 2, other-centric responders showed sensitivity to the configural cue, making longer and more complex trajectories on neither-aligned configurations. That cue also influenced how listeners interpreted the front - back terms. Our findings suggest that configural cues can promote an other-centric strategy and its stabilization, influence response dynamics selectively, and impact the interpretation of spatial language.